Libertarian paternalism is hard paternalism. (27th November 2017) - Ryan, Shane
Abstract: I argue that libertarian paternalism is in fact paternalism, or hard paternalism, rather than a form of soft paternalism. I do so on the basis of an analysis of the paternalist act according to which the paternalist act needn't violate the will of the agent who is the target of that act and the paternalist actor need only suspect that her action may improve the welfare of that target. The paper considers and rejects interpretations of libertarian paternalism as soft paternalism. I then provide an outline as to how libertarian paternalism may be reformed in light of the finding that current libertarian paternalism is hard paternalism. The proposal is to require that the enactment of libertarian paternalist policies be conditional on opinion polling indicating support for those policies from the agents they target.